New or otherwise interesting records of Pottiaceae (Bryophyta) for Peru - Ramos, Jorge L.; Cano, María J.; Jimenéz, Juan A.; Gallego, M. Teresa; Opisso, Jasmín A. (Phytotaxa, 2026)
Barbulastrum linearifolium, Husnotiella asperifolia, Leptodontium stellaticuspis, Mironia ehrenbergiana, Syntrichia ramosissima, S. robusta and Trichostomopsis challaensis are reported for the first time from Peru, and Bryoerythrophyllum recurvirostrum is new for the Neotropics. In addition, the distribution of Leptodontium proliferum and Tortula arequipensis in this country is updated.